1997
DOI: 10.1096/fasebj.11.8.9240970
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease inhibitors block neutral sphingomyelinase activation, ceramide generation, and apoptosis triggered by daunorubicin

Abstract: To address the role of a plausible protease cascade in daunorubicin-triggered apoptosis, we evaluated the effect of cell-permeant protease inhibitors on its signal transduction pathway. Treatment of U937 and HL-60 cells with 0.5-1 microM of the chemotherapeutic drug daunorubicin induced a greater than 30% activation of neutral sphingomyelinase activity within 4-10 min with concomitant sphingomyelin hydrolysis and ceramide generation. DNA fragmentation and the classical morphological features of apoptosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 0 publications
5
67
0
Order By: Relevance
“…49 Generation of ceramides has been already described with various chemotherapeutic agents. 25,27,28,30,38,50 Here we report that ETO and CPT increased the generation of ceramide in sensitive (activated) but not in resistant (resting) PBL. Ceramide production was maximal after 30 and 60 min of treatment with ETO or CPT, respectively, corresponding to the earliest signal observed in ETO-and CPT-induced apoptosis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…49 Generation of ceramides has been already described with various chemotherapeutic agents. 25,27,28,30,38,50 Here we report that ETO and CPT increased the generation of ceramide in sensitive (activated) but not in resistant (resting) PBL. Ceramide production was maximal after 30 and 60 min of treatment with ETO or CPT, respectively, corresponding to the earliest signal observed in ETO-and CPT-induced apoptosis.…”
Section: Discussionmentioning
confidence: 73%
“…50 Briefly, after 3 days of culture, 2610 7 PBL were starved for 2 h in RPMI containing 2% BSA and then treated with ETO, CPT or a CD95 agonistic mAb (7C11) for indicated time. …”
Section: Ceramide Measurementmentioning
confidence: 99%
“…1,2,5,45 TPCK and DCI, but not other cell-permeable protease inhibitors, have been shown to inhibit the generation of ceramide and apoptosis, by blocking daunorubicin-induced sphingomyelinase activation. 46 Also internucleosomal DNA fragmentation induced by the topoisomerase I inhibitor camptothecin was suppressed by TPCK in B lymphoma Namalwa cells 47 and HL60 cells, 1,48 but caspase-3-like activity and high molecular weight DNA fragmentation were not affected. 47 On the other hand, our work and that of others 9,10,49 shows that TPCK can clearly also induce apoptosis.…”
Section: Discussionmentioning
confidence: 94%
“…Although the role of serine proteases in cell death remains largely unexplored, a number of studies have shown that serine protease inhibitors can block apoptosis induced by certain stimuli Adjei et al, 1996, Dong et al, 1997Chow et al, 1995;Weis et al, 1995;Mansat et al, 1997;Shao et al, 1997). For example, TPCK has been shown to inhibit both FAS antigen-and p53-induced apoptosis as well as cell death occurring in response to various chemotherapeutic agents (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TPCK has been shown to inhibit both FAS antigen-and p53-induced apoptosis as well as cell death occurring in response to various chemotherapeutic agents (e.g. etoposide, UCN-01, and daunorubicin) in cells of hematopoietic origin Mansat et al, 1997;Shao et al, 1997;Sebestyen et al, 1997;Lotem and Sachs, 1996). TLCK on the other hand, was found to be e ective in inhibiting cell death by camptothecin and glycodeoxycholate in hepatocytes, but TPCK was without e ect (Kwo et al, 1995, Adjei et al, 1996.…”
Section: Discussionmentioning
confidence: 99%